1999
DOI: 10.1530/eje.0.1410231
|View full text |Cite
|
Sign up to set email alerts
|

Testicular adrenal rests: evidence for luteinizing hormone receptors and for distinct types of testicular nodules differing for their autonomization

Abstract: We report one patient with 21-hydroxylase deficiency and associated bilateral macro-orchidism caused by nodular hyperplasia of testicular adrenal rests (TAR). The boy, referred to us when 10 years old, was born with bilateral cryptorchidism that was treated unsuccessfully with i.m. injections of human chorionic gonadotropin (hCG) and later on with orchidopexy. He was treated with oral dexamethasone (0.625 mg per day) for the following 13 years.After one year, there was a marked reduction in steroid hormone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 8 publications
(13 reference statements)
4
28
1
2
Order By: Relevance
“…It can be suggested that hormones whose levels are increased in puberty, such as LH, are additional stimulators of tumour growth. The presence of LH receptors in testicular tumour tissue supports this hypothesis (24).…”
Section: Discussionmentioning
confidence: 61%
“…It can be suggested that hormones whose levels are increased in puberty, such as LH, are additional stimulators of tumour growth. The presence of LH receptors in testicular tumour tissue supports this hypothesis (24).…”
Section: Discussionmentioning
confidence: 61%
“…In multiple regression analysis, the maximal cross-sectional area of a TART was transformed to the logaels, the adrenal tissue remnants become hyperplastic and eventually develop tumors. Thus, TARTs are also found in other diseases with high ACTH levels, such as Nelson's syndrome and Cushing's disease [11], and the size of a TART is reduced by adequate suppression of ACTH secretion by treatment [12]. TARTs do not occur in patients with nonclassic or late-onset CAH, because ACTH level is not elevated enough [3].…”
Section: Statisticsmentioning
confidence: 99%
“…First, we excluded prepubertal patients in our study. ACTH, angiotensin II (AII), and luteinizing hormone (LH) are known as trophic factors of TARTs, and LH receptors may exist in testicular adrenal rest tissue [3,11]. Therefore, increased LH levels might promote the growth of a TART during puberty [11,17].…”
Section: Relationships Between the Maximal Cross-sectional Area Of Tamentioning
confidence: 99%
See 1 more Smart Citation
“…Como receptores LH são encontrados em HRA, isso poderia explicar o aumento da prevalência de HRA na puberdade e em pacientes pós-púberes com HAC, mesmo quando há bom controle hormonal (8). Assim, é possível que os tumores testiculares encontrados em pacientes portadores de HAC sejam resultantes da hiperplasia desse tecido adrenocortical ectópico na gônada estimulada pelos níveis elevados de ACTH e, provavelmente, também pelo LH e AII (3,8,10).…”
Section: Relato Do Casounclassified